Scaling Agricultural Technologies through Market Development: Examples from the Cereal Systems Initiative for South Asia. - McDonald, Andy. (Tufts University. Tisch Library., 2016)
This in-depth presentation details the ins and outs of several aspects in cereal market development. Delievered on Day 2 of the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Keywords: Bill & Melinda Gates Foundation.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy